Length weight relationship, condition factor and stomach contents of Hemichromis bimaculatus, Sarotherodon melanotheron and Chromidotilapia guentheri (Perciformes: Cichlidae) in Eleiyele Lake, Southwestern Nigeria - Ayoade, A. A. (2007)
Length-weight relationship (LWR), condition factor (K) and stomach content of three cichlid fishes (Hemichromis bimaculatus, Sarotherodon melanotheron, and Chromidotilapia guentheri) were calculated at Eleiyele reservoir, Nigeria, Africa. The fish were collected monthly from fishermen during the dry season(January-March 2001) and the rainy season (April, May, June 2001). Gill nets of mesh sizes 50-55 mm were used. The LWR had a significant correlation for the three species and the growth exponent (b) for H. bimaculatus indicates a negative allometric growth (S. melanotheron and C. guentheri had isometric growth). Condition factor values were higher than one in the three species, and varied with size and season. Stomach contents revealed that the three species are omnivorous and that diet composition varies seasonally. Rev. Biol. Trop. 55 (3-4): 969-977. Epub 2007 December, 28.